2012
DOI: 10.1371/journal.ppat.1002518
|View full text |Cite
|
Sign up to set email alerts
|

Concerted Actions of a Thermo-labile Regulator and a Unique Intergenic RNA Thermosensor Control Yersinia Virulence

Abstract: Expression of all Yersinia pathogenicity factors encoded on the virulence plasmid, including the yop effector and the ysc type III secretion genes, is controlled by the transcriptional activator LcrF in response to temperature. Here, we show that a protein- and RNA-dependent hierarchy of thermosensors induce LcrF synthesis at body temperature. Thermally regulated transcription of lcrF is modest and mediated by the thermo-sensitive modulator YmoA, which represses transcription from a single promoter located far… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
270
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 149 publications
(286 citation statements)
references
References 84 publications
15
270
0
1
Order By: Relevance
“…Several human pathogenic bacteria produce virulence-associated traits only under conditions of infection, and in various instances temperature has been shown to play a major role in the regulation of their expression (8)(9)(10). In these cases, the production of virulence determinants is completely abrogated at environmental temperatures (30°C or lower), whereas the genes encoding these factors are fully expressed at 37°C.…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…Several human pathogenic bacteria produce virulence-associated traits only under conditions of infection, and in various instances temperature has been shown to play a major role in the regulation of their expression (8)(9)(10). In these cases, the production of virulence determinants is completely abrogated at environmental temperatures (30°C or lower), whereas the genes encoding these factors are fully expressed at 37°C.…”
Section: Significancementioning
confidence: 99%
“…In these cases, the production of virulence determinants is completely abrogated at environmental temperatures (30°C or lower), whereas the genes encoding these factors are fully expressed at 37°C. In many organisms, the modulation of the expression of genes encoding virulenceassociated traits is achieved by RNA structures present in the 5′ untranslated region (UTR) of genes encoding key transcriptional regulators (10,11). Recently, it was reported that P. aeruginosa genes encoding virulence factors regulated by QS were induced at 37°C, the human body temperature (12); however, the molecular mechanism for this thermoregulation has not yet been determined.…”
Section: Significancementioning
confidence: 99%
“…Y. pseudotuberculosis is a foodborne pathogen closely related to Y. pestis and causes enteritis, diarrhea, and mesenteric lymphadenitis in animals and humans. Its metabolism and virulence are strictly temperature controlled by various posttranscriptional mechanisms (6,26). An intercistronic RNAT is present upstream of low calcium response gene F (lcrF) coding for the master regulator of Yersinia virulence (6).…”
mentioning
confidence: 99%
“…Surprisingly, so far only one RNAT has been identified and characterized in Y. pseudotuberculosis, the lcrF RNAT located in the intergenic region of the yscWlcrF operon [42] [44]. In addition to translation, the transcription of many RNAT-controlled genes (e.g.…”
Section: Rna Thermometers (Rnats)mentioning
confidence: 99%